The evolution of the International Cooperation for Development Policy of Mexico towards a State Policy - Soto, Fabiola; Castillo, Carlos (Revista Española de Desarrollo y Cooperación, 2021)
The implementation of the international cooperation for development policy is not an easy process for any country, especially for a middle-income and dual-nature country like Mexico. This article seeks to analyze the evolution of this policy from its design, as well as to identify the key elements for its eventual consolidation as a State Policy.